STUDIES ON PHYTOCHEMICAL SCREENING, ANTIOXIDANT ACTIVITY AND EXTRACTION OF ACTIVE COMPOUND (SWERTIAMARIN) FROM LEAF EXTRACT OF ENICOSTEMMA LITTORALE. - S, SELVARAJ; CV, CHITTIBABU; B, JANARTHANAM (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: The objective of the study was to evaluate the phytochemical constituents, total phenol, total terpenoid, antioxidant activity and HPLC analysis of swertiamarin compound from the leaf extract of Enicostemma littorale. Methods: Preliminary screening involved the qualitative methods to detect the presence of terpenoids, flavonoids, phenols, tannins, steroids, quinones, saponins, cardiac glycosides and alkaloids. Total phenol and terpenoid contents were quantitatively estimated. Total phenolic content was estimated by folin-ciocalteau method. In vitro antioxidant activity of petroleum ether, chloroform, acetone, aqueous and ethanol extracts was evaluated by studying 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activity using standard procedure. The leaf extract was screened for major metabolite namely swertiamarin compound using HPLC. Results: The phytochemical analysis of leaf extract of E. littorale revealed the presence of significant secondary metabolites such as steroids, quinones, cardiac glycosides, saponins, tannins, phenols, flavonoids, terpenoids and alkaloids. The total phenol and terpenoid content in leaf extract were found to be 16.32 mg GAE /g and 71.0 mg /g respectively. The acetone leaf extract of E. littorale had showed significant radical scavenging activity. The results of High Performance Liquid Chromatography analysis in the leaf extract of E. littorale proved the presence of the active principle namely swertiamarin. Conclusion: It can be concluded that E. littorale leaf extract can be used as a potent source of natural antioxidant and thus could prevent many free radical mediated diseases. The validated HPLC method can be used for a routine quality control analysis. Key words: Enicostemma littorale, antioxidant activity, phenols, terpenoids, phytochemical screening.